Cloud-Centric Architectures for Social Media: A Review of Challenges and Evolutionary Trends - Hina Rabbani,; Sana Rabbani,; Dr. Yusuf Perwej,; Farheen Siddiqui,; Dr. Nikhat Akhtar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Due to the many benefits it offers including scalable resources, cost savings, and improved operational performance cloud computing has quickly become an integral component of contemporary IT design. In today's digital world, social media platforms are indispensable. Everyone uses and shares material on platforms for various reasons, whether it's just to stay in contact for everyday communication or to reach a wider audience and learn about their thoughts and perspectives. This article delves deep into the world of cloud-based social media platforms, exploring their designs, the difficulties they face, and the trends that are only starting to emerge. To enable these platforms to manage different features and enormous user loads, we investigate the crucial role of cloud services (IaaS, PaaS, SaaS) and architectural patterns such as microservices and serverless computing. We will go over some of the main obstacles, such as keeping prices down, establishing good content control, handling privacy and security issues, and understanding data analytics. It goes on to talk about how serverless computing, containerization, and micro services design are becoming more popular, all of which help make cloud environments more agile and efficient with their resources. The survey also looks at how cloud computing relates to other cutting-edge innovation like Blockchains, machine learning, and artificial intelligence (AI). Finally, this research presents the most recent advancements, obstacles, and potential future directions in cloud computing, providing a thorough evaluation of the present status of the subject.
Keywords: Cloud Computing; Security Challenges; Social Media Platforms; Infrastructure; Artificial Intelligence; User Experience; Blockchains